Medical students’ academic motivation: an analysis from the perspective of the Theory of Self-Determination - Cadête Filho,Anizio de Almeida (2021)
Abstract: Introduction: The principles of the Theory of Self-Determination are relevant to professional education, as the differentiation and expression of the primary types of motivation have implications for the multiple learning outcomes. Objective: To evaluate academic motivation in 4th-year medical students at two teaching institutions and discuss the results from the perspective of the Theory of Self-Determination. Method: The present is a cross-sectional and quantitative study, conducted through a self-answered questionnaire containing 18 sociodemographic questions and the Academic Motivation Scale (AMS). The sample consisted of 147 4th-year medical students from schools with different teaching methodologies: 73 students from Institution A (Problem-based learning - PBL) and 74 students from Institution B (traditional methodology). A univariate analysis was conducted using Student’s t test, Analysis of Variance (ANOVA), chi-square test and Pearson’s correlation, followed by Multiple Linear Regression analysis. Results: There was a moderate profile of intrinsic (IM) and extrinsic (EM) motivation in the sample of students, with a higher IM than EM average. High levels of IM were observed in the domains of motivation for achievement and for knowledge, with the satisfaction of increasing one’s knowledge and increasing professional competence being the factors that most positively impacted motivation. In IM, the factor with the lowest score was the university as a place of enjoyment. EM was related to the desire of having a good life in the future, including monetary compensation. It was observed that the variables female gender, age under 23 years, living alone, having attended the entire course at the same institution and school with the PBL methodology had a positive influence on motivation. Conclusion: The students demonstrated higher levels of IM than those of EM, with a lower score attributed to the university as a place of enjoyment. This fact shows an opportunity for future studies, which will be able to verify the factors of the school environment related to the students’ motivation to learn. EM was associated with future life expectations. To know the variables that characterize the self-regulation of learning is crucial to support teaching strategies that contribute to the improvement of the teaching-learning process.